A study an impact of daylight with period time on illuminance and uniformity for building - Sripramong, S.; Ananwattanaporn, S.; Ngaopitakkul, A.; Jettanasen, C. (My University, 2015)
The daylight can be applied for lighting system in building to reduce energy consumption. Although the illuminance on the task area can be increased using the daylight but various factors must be taken into account. This research aims to study an impact of illuminance with daylight in term of each time period. The illuminance is calculated with daylight function in DIALux program. In addition, the fluorescent T5 tube lamp is used in simulation. The case study room without daylight (base case) is compared, in term of illuminance, with the case study room with daylight of each time period. The obtained results show that the daylight can increase the illuminance in the building so the lighting system in many modern buildings has applied daylight in order to achieve specific result of energy savings. The obtained results are useful for design of the interior lighting system.
Keywords: Daylight control; Energy saving; Fluorescent lamp; Illuminance; Lighting system